Examining the relationship between health literacy and quality of life in patients with coronary heart disease: a quantitative study at a cardiology clinic - Lita Lita; Nadila Khairiyah; Agnita Utami; Silvia Nora Anggreini; Faridah Mohd. Said (PAGEPress Publications, 2024)
Coronary Heart Disease (CHD) is the leading cause of death worldwide and is rising, annually. Improved health outcomes require early treatment and self-monitoring, which need health literacy. This study examined how health literacy affects CHD patients' Quality of Life (QoL) at the Hospital's Cardiology Clinic. This quantitative, descriptive correlation study was cross-sectional. The sample was 164 respondents, sampled consecutively. Patients must be willing to participate, diagnosed with CHD, and attend cardiology outpatient follow-up appointments. Health literacy was measured with the HLS-EU-SQ10 and QoL with the Seattle Angina Questionnaire. This study used chi-square to analyze the relationship between two ordinal scale variables in a contingency table. The average age was 58.07 years, according to research. Of the respondents, 59 (36.0%) had graduated high school. Health literacy was assessed in three QoL domains: physical limitation (P=0.024), angina frequency (P=0.570), and QoL (P=0.338). Service agencies should be able to use pamphlets to improve health literacy and provide rehabilitation to acute coronary syndrome patients to improve QoL.